ACHIVEMENTS OF BREEDING PROGRAM FOR SPICY FLAVOURING AND AROMATIC PLANTS - V.A. Kharchenko (Овощи России, 2011)
The last 10 years achievements of breeding program for spicy, flavouring and aromatic plant crops at All-Russian Research Institute of Vegetable Breeding and Seed Production (VNIISSOK) are shown. The concise descriptions of some horticulturally valuable traits among new developed varieties selected at VNIISSOK were given.